TRANSMISSION OF LONGITUDINAL WAVES IN LOAMY SOILS UNDER THE WIDE RANGE OF HUMIDITY (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
The increase of humidity in loamy soils generally has a double influence on velocity of transmission of longitudinal waves (Vp). On the one hand the increase of soil humidity brings to reduction of the volume of pores the result of which is the increase of Vp velocity through the soil medium. On the other hand the increase of humidity depending on initial humidity and degree of saturation might result in reduction of soil solidity and consequently to reduction of velocity Vp. Characteristic indexes of soil humidity, when increase of those brings to the constancy of modification of the slip resistance (shear strength) and changes the velocity of transmission of longitudinal waves (Vp) have been stated by experimental investigations. Basing these experiments, the correspondence of the upper limit of «paradoxical» interval of humidity and the lower limit of plasticity has been established.
Keywords: longitudinal waves; loamy soils; «paradoxical» interval of humidity